Soil Characterization of Kanker District: A Transect Study along a Toposequence - N. Kumar (Journal of the Indian Society of Soil Science, 2023)
Pedological investigation carried out on a soil toposequence of Bastar Plateau in Kanker district ofChhattisgarh state and landform-soil relationships were established. Five soil profiles, representative of thesummit, shoulder slope, pediments and upper and lower pediplains in a toposequence were studied. Thestudy indicated that the soil development and its properties were following the toposequence. The profiledevelopment was least at the summit and best in the pediplains of the toposequence. The horizon sequencesobserved were Ap-Cr, Ap-Bw-BC, Ap-Bw-Cr and Ap-Bw-Bss from summit through the pediplains. Thesoil colour varied from reddish to dark gray down the toposequence. The solum depth varied from extremelyshallow to very deep. An increasing trend was observed in clay content, cation exchange capacity, soilreaction, electrical conductivity, base saturation, and exchangeable cations from summit through thepediplains. The soils of summit, pediments and pediplains were classified as Entisols, Inceptisols andVertisols, respectively.